Inhibition of histone deacetylase 4 increases cytotoxicity of docetaxel in gastric cancer cells. Issue 11 (22nd October 2014) - Colarossi, Lorenzo; Memeo, Lorenzo; Colarossi, Cristina; Aiello, Eleonora; Iuppa, Antonio; Espina, Virginia; Liotta, Lance; Mueller, Claudius; Everett, Allen; Ignjatovic, Vera
<x xml:space="preserve">Abstract</x> Purpose New treatment options for gastric cancer are in great demand. Histone deacetylases (HDACs) are exciting therapeutic targets, but only the class I HDACs 1, 2, and 3 have been studied in gastric cancer. We have investigated class IIa HDAC expression and inhibition in gastric cancer cells. Experimental design We measured the level of 27 (phospho)proteins related to class IIa HDAC expression and function in ten laser‐capture microdissection gastric tumor samples compared to patient‐matched adjacent normal mucosa. Following, we evaluated class IIa HDAC inhibition by MC1568 in SNU‐16 gastric cancer cells alone and in combination with cisplatin or docetaxel. Results We demonstrate for the first time an increase of HDAC4 in gastric tumor cells. HDAC4 inhibition had a synergistic effect with docetaxel treatment, shifting the cellular response from a cytostatic to a cytotoxic phenotype. This effect was associated with increased levels of cleaved caspases 3 and 9 and increased acetylated histone H3 Lys9/Lys14. Conclusions and clinical relevance These data support in vivo studies investigating the potential clinical use of HDAC4 inhibitors in combination with docetaxel for the treatment of gastric cancer, lowering treatment doses of docetaxel to reduce the burden of adverse side effects on patients.